Organisasi dan Desain Pengembangan Kurikulum - Wahyu Aprilia (Pendidikan Agama Islam STIT Palapa Nusantara, 2020)
The world of education cannot ber separated from the curriculum. The curriculum is one of the most important components of education. The curriculum can cover a broad scope and a narrow scope. A curriculum must have compatibility or relevance with the needs and demands that exist in society. The curriculum must also be able adjust the components in it. In its implementation in a educational institution, the curriculum needs to be developed, in developing a curriculum it certainly cannot be done just like that without reference or guidance. One of the curriculum that is developed must pay attentiom to the organization and design of curriculum development. The organization and design of the curriculum is one aspect that needs to be considered so that in curriculum sevelopment it can meet all the needs and demand of students, educators, and also the community. This study uses the library research method by examining several data sources from books relating to the organization and curriculum development design. The conclusion of this study is that in the process of developing the organizational curriculum it acts as a method for determining the selection and integration of learning experiences held by educational institutions. An organization is very necessary for the management process, namely planning organizations, organizations in the framework or curriculum implementation, and organizations in the framework of curriculum evaluation. In developing curriculum, curriculum design is also needed. Curriculum design is the organization of goals, content, and processes that students will undergo in an educational institution. There are various designs that have been compiled and each design has certain strengths and weaknesses. This study can be a reference for institutions that want to develop a curriculum to understand what organizations and design developments fit their needs. Future research is expected to be able to deal more deeply with the organization and design or curriculum development.